A novel RT‐PCR method for quantification of human papillomavirus transcripts in archived tissues and its application in oropharyngeal cancer prognosis. Issue 4 (7th September 2012) - Gao, Ge; Chernock, Rebecca D.; Gay, Hiram A.; Thorstad, Wade L.; Zhang, Tian R.; Wang, Hongwei; Ma, Xiao‐Jun; Luo, Yuling; Lewis, James S.; Wang, Xiaowei
Abstract Oropharyngeal squamous cell carcinoma (SCC) is strongly associated with human papillomavirus (HPV) infection, which is distinctively different from most other head and neck cancers. However, a robust quantitative reverse transcription PCR (RT‐qPCR) method for comprehensive expression profiling of HPV genes in routinely fixed tissues has not been reported. To address this issue, we have established a new real‐time RT‐PCR method for the expression profiling of the E6 and E7 oncogenes from 13 high‐risk HPV types. This method was validated in cervical cancer and by comparison with another HPV RNA detection method (in situ hybridization) in oropharyngeal tumors. In addition, the expression profiles of selected HPV‐related human genes were also analyzed. HPV E6 and E7 expression profiles were then analyzed in 150 archived oropharyngeal SCC samples and compared with other variables and with patient outcomes. Our study showed that RT‐qPCR and RNA in situ hybridization were 100% concordant in determining HPV status. HPV transcriptional activity was found in most oropharyngeal SCC (81.3%), a prevalence that is higher than in previous studies. Besides HPV16, three other HPV types were also detected, including 33, 35 and 18. Furthermore, HPV and p16 had essentially identical expression signatures, and both HPV and p16 were prognostic biomarkers for the prediction of disease outcome. Thus, p16 mRNA or protein expression signature is a sensitive and specific surrogate marker for HPV transcriptional activity (all genotypes combined).